Pengaruh Paraquat Dan Kelengasan Terhadap Dinamika Nitrogen Pada Vertisol = Influence of Paraquat and Moisture Contents on The Dynamic of Nitrogen in Vertisol - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Abstract The purpose of this study was to investigate the influences of paraquat and moisture contents on the dynamics of nitrogen in Vertisol from Lombok Island. Research was done in Laboratory of the General Soil Science and Central Laboratory of Chemistry and Physics, Gadjah Mada University. Pot experiment were arranged in Complete Randomized Design (CRD) factorial with three replications. The first factor was level of moisture contents namely field capacity and flooded at 5 cm. The second factor was paraquat concentration with three levels of 0,100 and 1000 ppm. The treatments were incubated within 90 days at room temperature. Periodically, every 10 days, the soil chemical properties were analyzed especially its nitrogen compounds' content. The results showed that interaction between of paraquat and moisture contents significantly influenced NH4* concentrations. The highest treatment of paraquat and flooded condition soil enhanced NH4* contents in vetisol. Nitrate (NO3) contents was influenced significantly by moisture contents. The low oxygen concentration in flooded water inhibited biooxidation of NH4* (nitrification). However, paraquat concentration was not influenced NO.' concentration. It was suggested that paraquat tightly bound to montmorillonite clay of Vertisol. Therefore, the bioavailability of residual paraquat in vertisol was very low.